1997
DOI: 10.1016/s0008-6363(96)00187-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhibition of sarcoplasmic reticulum calcium uptake on contraction in myocytes isolated from failing human ventricle

Abstract: Objectives: There has been debate regarding the level of sarcoplasmic reticulum (SR) Ca2+ATPase protein in heart failure. We have used the SR Ca2+ATPase inhibitor thapsigarginto investigatethe functionalcontributionof this uptake system to contractionand relaxation in myocytes from failing and non-failinghuman ventricle. Methods: Myocytes were isolated from 28 failing and 18 non-failingventriclesand stimulatedat 0.2 Hz, 32°Cin Krebs-Henseleit solution.Contractionamplitudeand speed were compared before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
2
17
0
3
Order By: Relevance
“…This data suggest a slowing of Ca 2+ -removal from the cytoplasm, whereby an impairment of the sarcoplasmic reticulum calcium ATPase (SERCA) [29], as reported for oxidative stress [31], is the most likely explanation. Such a SERCA impairment would subsequently lead to a decrease of calcium release which may account for the slowing in contraction onset, whereas a possible dysfunction of Ca 2+ release [28] may also play a role.…”
Section: Discussionsupporting
confidence: 51%
“…This data suggest a slowing of Ca 2+ -removal from the cytoplasm, whereby an impairment of the sarcoplasmic reticulum calcium ATPase (SERCA) [29], as reported for oxidative stress [31], is the most likely explanation. Such a SERCA impairment would subsequently lead to a decrease of calcium release which may account for the slowing in contraction onset, whereas a possible dysfunction of Ca 2+ release [28] may also play a role.…”
Section: Discussionsupporting
confidence: 51%
“…Cardiac excitation-contraction (E-C) coupling involves a tightly regulated sequential series of events which results in the cyclical increase in free intracellular [4][5][6], and numerous genes involved in calcium homeostasis have been reported to be altered in heart failure. For example, many studies show the downregulation of SERCA in both animal models [7] and human tissue samples from failing heart [8]. Borlak and Thum [9] have shown that in human end stage heart failure, left ventricular expression of PMCA1, PMCA4, and SERCA2 is reduced to 30%, 50%, and 30%, respectively, compared with the controls.…”
Section: Alterations In Calcium Homeostasis Are Associated With Heartmentioning
confidence: 99%
“…Again, observations were subject to controversy; some indicating depressed SERCA2a protein w x w x levels 7,14 and others showing no changes 8,9,15 . Additionally, some alternative functional approaches to investigate SERCA2a involvement in altered contractile function have shown that the calcium sequestering function of the sarcoplasmic reticulum is affected in human w x heart failure 8,11,12,[16][17][18][19][20][21] . A chronological summary of the findings related to alterations of SERCA2a in human heart failure is given in Table 1.…”
Section: Introductionmentioning
confidence: 99%